2013
DOI: 10.1016/j.bbmt.2013.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Photopheresis versus Anticytokine Therapy as a Second-Line Treatment for Steroid-Refractory Acute GVHD: A Multicenter Comparative Analysis

Abstract: The optimal therapy for steroid-refractory (SR) acute graft-versus-host disease (aGVHD) is undefined. We studied patients with SR aGVHD, comparing extracorporeal photopheresis (ECP; n = 57) and anticytokine therapy (n = 41). In multivariate analyses, ECP, adjusted for steroid dose (odds ratio, 3.42; P = .007), and grade >II aGVHD (odds ratio, 68; P < .001) were independent predictors of response. ECP therapy, adjusted for conditioning regimen intensity and steroid dose, was associated with superior survival (h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
1
3

Year Published

2014
2014
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 17 publications
7
45
1
3
Order By: Relevance
“…A multicenter retrospective study in patients with SR acute GVHD showed a higher response rate to ECP than to anti-cytokine therapy, which translated into an overall survival benefit. 27 The cumulative 2-year NRM rate in patients who achieved 6-month FFTF was 22.4%, with infections accounting for 6.6% of the deaths. This suggests that ECP does not cause generalized immunosuppression leading to an increased risk of severe opportunistic infections.…”
Section: Discussionmentioning
confidence: 96%
“…A multicenter retrospective study in patients with SR acute GVHD showed a higher response rate to ECP than to anti-cytokine therapy, which translated into an overall survival benefit. 27 The cumulative 2-year NRM rate in patients who achieved 6-month FFTF was 22.4%, with infections accounting for 6.6% of the deaths. This suggests that ECP does not cause generalized immunosuppression leading to an increased risk of severe opportunistic infections.…”
Section: Discussionmentioning
confidence: 96%
“…121,122 Other immunosuppressants available include anti-IL-2 receptor-, anti-IL6 receptor-, anti-CD20-, and anti-CD52-targeted therapies. There is some data in support of extracorporeal photopheresis 123 and infusion of mesenchymal stromal cells (MSCs) 124 in refractory aGVHD. Current clinical trials available for the treatment of steroid-refractory aGVHD include a combination of basiliximab plus infliximab (combined targeting of the IL-2 receptor and TNFa, NCT01485055).…”
Section: Refractory and Steroid-resistant Agvhdmentioning
confidence: 99%
“…20 ECP is successfully used to treat established acute and chronic GVHD especially in patients unresponsive to conventional immunosuppressive drugs and has been proven successful in prevention of solid organ rejection. [21][22][23] We hypothesized that administration of apoptotic cells prior to transplantation would induce unresponsiveness in the majority of immature DCs, consequently limit donor T-cell activation, and hence The online version of this article contains a data supplement.…”
Section: Introductionmentioning
confidence: 99%